2019
DOI: 10.1007/s00382-019-04758-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of freshwater release in the Mediterranean Sea on the North Atlantic climate

Abstract: Sediment cores from the Mediterranean Sea have evidenced several periods of Sapropel deposition, which can be explained by events of anoxic bottom conditions. An explanation for such events calls for a very stratified sea, possibly related with freshwater input through increased precipitations and runoff discharges. It has been suggested that such a stratified Mediterranean Sea may in turn weaken the Atlantic meridional overturning circulation (AMOC) through changes in the Mediterranean overflow water (MOW). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Paleoceanography and Paleoclimatology of the Atlantic and consequently on Atlantic Meridional Overturning Circulation (AMOC) and heat transport to the high latitudes Ivanovic et al, 2014;Kida et al, 2008;Ozgokmen et al, 2001;Rahmstorf, 1998;Reid, 1979;Rogerson et al, 2006;Swingedouw et al, 2019). On the other hand, changes in the AMOC and the physical properties of the Atlantic intermediate and deep water masses could also affect the MOW settling depth in the Atlantic.…”
Section: 1029/2020pa003931mentioning
confidence: 99%
See 1 more Smart Citation
“…Paleoceanography and Paleoclimatology of the Atlantic and consequently on Atlantic Meridional Overturning Circulation (AMOC) and heat transport to the high latitudes Ivanovic et al, 2014;Kida et al, 2008;Ozgokmen et al, 2001;Rahmstorf, 1998;Reid, 1979;Rogerson et al, 2006;Swingedouw et al, 2019). On the other hand, changes in the AMOC and the physical properties of the Atlantic intermediate and deep water masses could also affect the MOW settling depth in the Atlantic.…”
Section: 1029/2020pa003931mentioning
confidence: 99%
“…It spreads between 500 and 1,500 m and can eventually reach the high latitudes of the North Atlantic (Bashmachnikov et al, 2015; Bryden & Stommel, 1984; Iorga & Lozier, 1999; Mauritzen et al, 2001; Ozgokmen et al, 2001; van Aken, 2000a). Any change in the physicochemical properties of this water mass in response to Mediterranean pumping of heat and salt may have an important impact on the vertical density gradient of the Atlantic and consequently on Atlantic Meridional Overturning Circulation (AMOC) and heat transport to the high latitudes (Bethoux et al, 1999; Ivanovic et al, 2014; Kida et al, 2008; Ozgokmen et al, 2001; Rahmstorf, 1998; Reid, 1979; Rogerson et al, 2006; Swingedouw et al, 2019). On the other hand, changes in the AMOC and the physical properties of the Atlantic intermediate and deep water masses could also affect the MOW settling depth in the Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…MOW provides a salt source for intermediate depths of the North Atlantic, but the effects of this input are not well understood. It is widely (but not universally) suggested that the salt supplied by MOW significantly increases the rate of North Atlantic overturning today and had variable impacts during the last glacial cycle (Bahr et al, 2018; Llave et al, 2006; Rogerson et al, 2010, 2012; Swingedouw et al, 2019; Voelker et al, 2006). MOW probably exerts significant circulatory impact following Greenland stadials, forming a crucial part of the negative feedback mechanism that promotes the reinstatement of vigorous North Atlantic deepwater formation and overturning from its weakened cold‐interval state (Llave et al, 2006; Voelker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, significant reorganizations of shallow and intermediate water mass structure in the North Atlantic may arise in response to changes in MOW‐injection depth (Ivanovic, Valdes, Flecker, et al, 2013; Ivanovic, Valdes, Gregoire, et al, 2013) and the strength of the Azores Current, and consequently, European ice sheet dynamics are sensitive to MOW entrainment into North Atlantic intermediate water masses (Kaboth‐Bahr et al, 2018). In contrast to the idea that increased MOW‐fed salinity to the North Atlantic enhances overturning circulation, one recent numerical analysis of the impact of sapropel events suggests that the upper AMOC cell may weaken or strengthen, depending on the rate of freshwater input to the Mediterranean (Swingedouw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…jussieu.fr/igcmg_doc/wiki/Doc/Models/LMDZ (last access: May 2020) and http://forge.ipsl.jussieu.fr/nemo/wiki/Users (last access: May 2020) under the terms of the CeCill license for both LMDZ and NEMO. The exact version of the model used to produce the results used in this paper is archived on Zenodo (Vadsaria et al, 2019), as are input data and scripts to run the model and produce the plots for all the simulations presented in this paper.…”
mentioning
confidence: 99%